Capsule Endoscopy for Crohn’s Disease: Current Status of Diagnosis and Management - Dong-Hoon Yang; Bora Keum; Yoon Tae Jeen (Gastroenterology Research and Practice)
Crohn’s disease (CD) is an idiopathic inflammatory bowel disease involving the small and/or large intestine. More than 50% of Western CD patients and up to 88% of Asian CD patients may have small intestinal involvement. Video capsule endoscopy (VCE) has a higher diagnostic yield than small bowel barium radiography and computed tomography enterography for the detection of small intestinal involvement of CD. VCE also provides diagnostic yields comparable to magnetic resonance- (MR-) based enterography or enteroclysis and may have several advantages over MR-based tests for the detection of early small intestinal lesions. Several studies have suggested the use of VCE-based disease activity scoring systems to evaluate small intestinal mucosal disease activity, although their clinical relevance needs to be further studied. A possible indication for VCE is recurrence monitoring after complete surgical excision of CD-involved segments but its usefulness and efficacy compared with conventional endoscopy should be evaluated. The capsule retention rate ranges from 0 to 5.4% in suspected CD patients and from 0 to 13.2% in established CD patients. If VCE is necessary, significant small bowel stricture should be ruled out before VCE by performing a patency capsule study and/or small bowel radiological study in suspected or established CD patients.